Analisis Perhitungan Laba Usaha pada UMKM Papa Fries dengan Perbandingan Metode Biaya Absorpsi dan Biaya Marginal - Purwanti Purwanti; Devy Erviana Safitri; Andri Irawan (Pusat Riset dan Inovasi Nasional, 2025)
This reseacrh to examie the operating profit of the Papa Fries by comparing the absorption costing method with the marginal costing method. A qualitative research approach was employed, with the business owner. The findings indicat that The outcome of the marginal costing method is higher operationg profit compared to the absorption costing method. This outcome is attributed to the exclusion of fixed costs in the marginal costing calculation. Thesse result may provide useful insights for MSME practitioners in selecting the most appropriate costing method when establishing and managing a business.